Prediction of Surface Roughness of Ti-6Al-4V In Electrical Discharge Machining: A Regression Model - M., Ishak; Khan, Md. Ashikur Rahman; M. M., Rahman; K., Kadirgama; M. A., Maleque (Faculty Mechanical Engineering, UMP, 2011)
This paper develops a single order mathematical model for correlating the various electrical discharge machining (EDM) parameters and performance characteristics utilizing relevant experimental data as obtained through experimentation. Besides the effect of the peak ampere, pulse on time and pulse off time on surface roughness has been investigated. Experiments have been conducted on titanium alloy Ti-6Al-4V with copper electrode retaining negative polarity as per Design of experiments (DOE). Response surface methodology (RSM) techniques are utilized to develop the mathematical model as well as to optimize the EDM parameters. Analysis of Variance (ANOVA) has been performed for the validity test of fit and adequacy of the proposed models. It can be seen that increasing pulse on time causes the fine surface until a certain value and afterward deteriorates in the surface finish. The excellent surface finish is investigated in this study in the case of the pulse on time below 80 >s. This result guides to pick the required process outputs and economic industrial machining conditions optimizing the input factors.